THRIVING ABROAD: THE PSYCHOLOGICAL NEEDS OF INTERNATIONAL SCHOOL TEACHERSCC - Rana J Cheatwood (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study examined the basic psychological needs of international school teachers, emphasizing the challenges of living and working abroad within the framework of the Basic Psychological Needs Theory. The problem addressed in this qualitative, phenomenological study is the unfulfilled basic psychological needs of international school teachers in Southeast Asia. The research aimed to understand their lived experiences and how their needs were addressed, as reflected in the fulfilment of basic psychological needs. A qualitative phenomenological approach focused on the experiences of participants with varied backgrounds and experiences who were selected from a population of international school teachers in Southeast Asia. The data analysis procedure involved a systematic approach of coding and theme development from the in-depth interviews to explore the nuanced aspects of teachers' experiences, frustrations, and strategies for fulfilling their psychological needs. Key findings highlighted the essential role of meeting the psychological needs of autonomy, competence, and relatedness in enhancing teachers' well-being. The study also emphasized the importance of physiological needs and fostering a sense of belonging through meaningful relationships. Recommendations for school administrators include establishing Professional Learning Communities, regular mental health check-ins, and integrating the Basic Psychological Needs Theory in orientation programs and work culture. Addressing job insecurity and adapting to new cultural and educational systems emerged as challenges, underscoring the need for transparent communication and resources for maintaining work-life balance. The study offers valuable insights into the psychological well- being of international school teachers, emphasizing the importance of a supportive and inclusive work environment.